Inventing the "Great Awakening" - Lambert, Frank, 1943- (Princeton University Press, 1999)
This book is a history of an astounding transatlantic phenomenon, a popular evangelical revival known in America as the first Great Awakening (1735-1745). Beginning in the mid-1730s, supporters and opponents of the revival commented on the extraordinary nature of what one observer called the "great ado," with its extemporaneous outdoor preaching, newspaper publicity, and rallies of up to 20,000 participants. Frank Lambert, biographer of Great Awakening leader George Whitefield, offers an overview of this important episode and proposes a new explanation of its origins
Keywords: Great Awakening.; Revivals -- New England -- History -- 18th century.; Revivals -- New Jersey -- History -- 18th century.; Grand Réveil.; Réveils (Religion) -- Nouvelle-Angleterre -- Histoire -- 18e siècle.; Réveils (Religion) -- New Jersey -- Histoire -- 18e siècle.; 11.59 church history, history of doctrine: other.; 15.85 history of America.; HISTORY -- United States -- Colonial Period (1600-1775); Great Awakening; Revivals; New England; New Jersey; The Great Awakening; Geschichte 1730-1745.; 1700-1799; Acts of the Apostles.; Antinomianism.; Baptists.; Boston.; Bristol.; Calvinism.; Concert for Prayer.; Congregationalists.; Cross, Robert.; Cummings, Archibald.; Davidson, Henry.; Deism.; Dickinson, Jonathan.; Edinburgh.; Edwards, Timothy.; Enlightenment.; Fielding, Henry.; Foxcroft, Thomas.; Gentleman's Magazine.; Glasgow Weekly History.; Gooch, William.; Hamilton, Dr. Alexander.; Historical Collections.; Huguenots.; Independents.; Kilsyth, Scotland.; London Gazette.; Mather, Increase.; New Lights.; New York Gazette.; Nova Scotia.; Old Lights.; Parkman, Ebenezer.; Pentecost.; Pietism.; Quakers.; Ramism.; bank war.; church census.; conversion narratives.; counterinventions.; declension of religion.; enthusiasm.; experimental Christianity.; invention.; itinerancy.; jeremiad.; letter-writing network.; moderates.; numeracy.; practice of piety.; predestination.; History